Study guide for LPIC-1 exam 101-400 : preparing yourself to pass Part 1 of the LPIC-1 certification test - Jordan, Ted (O'Reilly, 2017)
"Are you ready to move ahead in a career as a Linux system administrator? Do you have basic experience installing software on Windows or Mac computers? Do you know how to change directories, read documents, and compress files? Then you have the knowledge necessary to take this course which provides all the information you need to pass the LPIC-1 101-400 exam. The 101-400 is the first of two exams you must pass to earn a LPIC-1 Linux administrator certification from the Linux Professional Institute. The LPIC-1 certification is respected by employers everywhere including CERN, DOD, NASA, NSA, and FAA. Holding the LPIC-1 tells the world you have the skill and knowledge to set up, maintain, and secure Linux systems."--Resource description page.